2017
DOI: 10.19041/apstract/2017/3-4/11
|View full text |Cite
|
Sign up to set email alerts
|

Protected geographical indication recognition and willingness to pay: A case of grojec apple

Abstract: The Grojec region of Poland is an important region for apple production and accounts for 40 percent of domestic apple production. Apple growers from the region made an attempt to strengthen their competitive position through registering their apples as Protected Geographical Indication (PGI) products. The European Commission’s PGI allows food producers to obtain market recognition and a premium price for their products. Although the Grojec Apple received PGI registration in 2011, little has been done to promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Nevertheless, the lowest PP dispersion is observed among organic products, whereas within GI it is very high, especially for PGI. The findings showing a positive price premium are consistent with the results of numerous studies conducted at retail level which exhibit a consumer's willingness to pay (WTP) for organic food (Dimitri and Dettman, 2012;Maigné et al, 2017;Wier et al, 2008), PDO products (Fotopoulos and Krystallis, 2003;Garavaglia and Mariani, 2017;Panin et al, 2015) and PGI products (Ahrendsen and Majewski, 2017). This study demonstrates that this WTP is carried through all the supply chain, with significant PP at upstream and processing level, regardless of product categories.…”
Section: Price Premium Distribution By Sectorsupporting
confidence: 88%
See 1 more Smart Citation
“…Nevertheless, the lowest PP dispersion is observed among organic products, whereas within GI it is very high, especially for PGI. The findings showing a positive price premium are consistent with the results of numerous studies conducted at retail level which exhibit a consumer's willingness to pay (WTP) for organic food (Dimitri and Dettman, 2012;Maigné et al, 2017;Wier et al, 2008), PDO products (Fotopoulos and Krystallis, 2003;Garavaglia and Mariani, 2017;Panin et al, 2015) and PGI products (Ahrendsen and Majewski, 2017). This study demonstrates that this WTP is carried through all the supply chain, with significant PP at upstream and processing level, regardless of product categories.…”
Section: Price Premium Distribution By Sectorsupporting
confidence: 88%
“…Several studies mobilized purchasing records and surveys to determine consumers' WTP for PDO/PGI. Most of them dealt with a single product: Fotopoulos and Krystallis (2003) analysed the PDO Zagora apples in the Greek market; Ahrendsen and Majewski (2017) focused on the Protected Geographical Indication Recognition and the WTP for Grojec Apple; Garavaglia and Mariani (2017) analysed the case of PDO Dry-Cured Ham in Italy. In relation to organic products, Dimitri and Dettmann (2012) studied consumers' behaviour regarding three product categories (vegetable, fruit and milk).…”
Section: Expansion and Global Economic Impacts Of The Main Fqs In Europementioning
confidence: 99%
“…Consumers agree with the proposition that "products with GI contributes to the producer and the economy of the region" (3.95), "products with GI is more reliable" (3.68), "consume products with GI in the future" (3.66) and "products with GI is of higher quality" (3.64), respectively (Table 3). In the studies conducted, consumers found that geographically marked product were superior to others (Van Ittersum et al, 2000;Teuber, 2011;Vecchio and Annunziata, 2011;Verbeke et al, 2012;Likoudis et al, 2016;Kokthi et al, 2016;Ahrendsen and Majewski, 2017;Kos Skubic et al, 2018;Roselli et al, 2018;Dokuzlu et al, 2020;Lee et al, 2020;Lu and Saijiki, 2021).…”
Section: Consumption Of Foods With Gismentioning
confidence: 98%
“…A rising part of the population is concerned about food safety and quality and considers provenance to be a helpful quality indicator (Teuber, 2011). Consumers believe that products with GI have superior quality and taste compared to other products (Van Ittersum et al, 2000;Teuber, 2011;Vecchio and Annunziata, 2011;Verbeke et al, 2012;Meral and Şahin, 2013;Likoudis et al, 2016;Ahrendsen and Majewski, 2017;Kos Skubic et al, 2018;Roselli et al, 2018). The fact that products with GI inform consumers about the reliability, quality and origin of the product causes the consumers to increase the price they are willing to pay (Bramley et al, 2009;Vecchio and Annunziata, 2011;Aprile et al 2012;Deselnicu et al 2013;Lefèvre, 2014;Bishop and Barber, 2015;Lu and Sajiki, 2021;Zhang et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Yeon et al [29] conducted an experiment with students in their acceptance of fresh apples, and came to the conclusion that students are willing to pay more for apples if they are bigger and crispier. Ahrendsen and Majewski [30] investigated how consumers accept apples from the Gorjec region in Poland. They proved that there would be better acceptance and greater willingness to pay a higher price for these apples if it were stated that they are protected geographical indication products.…”
Section: Banihabib and Shabestarimentioning
confidence: 99%